Exploration of Phrasal Verbs in ELT Textbooks: A Corpus-Based Analysis of Lower Secondary Level Bangladeshi Books - Naywaz Sharif Shubha (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The study aims at exploring the usage of the Phrasal Verbs in the lower secondary Bangladeshi ELT textbooks which are prescribed by the Government of Bangladesh at national education levels. The methodological approach continues in this study based on the corpus tools and related analysis on the topic of Phrasal Verbs usage in those textbooks. The phrasal verbs that are found in the textbooks are extracted from the textbooks; their frequency distributions are analyzed, and finally checked with the two most authentic corpus of the English Language - The British National Corpus (BNC) and Corpus of Contemporary American English (COCA). Alongside, deriving the top fifteen Phrasal Verbs in the textbook corpus with their significant values; the relative positions to the two reference corpora and other corpus-related scores of the phrasal verbs are compared, regarding the study of Liu (2011). The results find that the Phrasal Verbs used in the selected textbooks are quite irrelevant to the two standard big corpora. Finally, based on the findings some remarks and implications are prescribed for pedagogical purposes. The current study would be the first one that examines the Bangladeshi Lower Secondary ELT textbooks assisted by the corpus approach.